The Influence Of Green Marketing and Green Brand Image nn Green Satisfaction Starbucks Yogyakarta - Yoga Pranata; Sri Rejeki Ekasasi (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to find out the impact of green marketing and green brand image on consumers’ green satisfaction Starbucks Yogyakarta. This research method uses a quantitative method assisted by the analysis of SPSS for windows 25. The sampling technique used is a non-probability sampling method with a purposive sampling method with 100 consumers of Starbucks Yogyakarta as respondents. The results of this study show that partially there is a significant positive influence between the green marketing variables toward green satisfaction. and a significant positive influence between the green brand image variables on green satisfaction. In addition, there is also a simultaneous influence between green marketing and green brand image on the green satisfaction of Starbucks Yogyakarta consumers.